2017
DOI: 10.1080/14712598.2018.1389885
|View full text |Cite
|
Sign up to set email alerts
|

The potential of solanezumab and gantenerumab to prevent Alzheimer’s disease in people with inherited mutations that cause its early onset

Abstract: The recent failure of several clinical trials on anti-β-amyloid (Aβ) drugs in Alzheimer's disease (AD) suggested earlier intervention in the disease course. Secondary prevention trials have been started in autosomal-dominant AD (ADAD) individuals without cognitive dysfunction and in cognitively healthy subjects at risk of developing sporadic AD (SAD). Areas covered: Herein, the authors discuss prevention trials in ADAD and SAD, with a focus on the anti-Aβ monoclonal antibodies solanezumab and gantenerumab pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 87 publications
0
22
0
4
Order By: Relevance
“…Panza et al showed the trial design to evaluate whether solanezumab and gantenerumab could prevent AD in its early onset for people with autosomaldominant AD or cognitively healthy subjects at risk of developing sporadic AD [58].…”
Section: Pharmaceutical Neurorestorative Therapymentioning
confidence: 99%
“…Panza et al showed the trial design to evaluate whether solanezumab and gantenerumab could prevent AD in its early onset for people with autosomaldominant AD or cognitively healthy subjects at risk of developing sporadic AD [58].…”
Section: Pharmaceutical Neurorestorative Therapymentioning
confidence: 99%
“…I ir II fa ziø ty ri muo se ne bu vo ste bë ta sunkiø ne pa gei dau ja mø reið ki niø, kaip, pa vyz dþiui, tai kant ak ty vià imu no te ra pi jà vak ci na. Vi si iki ðiol su AL at lik ti III fa zës di de lës ap im ties kli ni ki niai ty ri mai (EXPEDITION1, EXPEDITION2, EXPEDITION3 ir ExpeditionPRO) ne pa ro dë pra na ðu mo prieð pla ce bo [32]. Ðiuo me tu ðis vais tas ne be ti ria mas AL pa cien tams su nusta ty ta de men ci ja, ta èiau pra dë ti pre ven ci niai ty ri mai [14].…”
Section: Amiloido Beta ðAlinimo Skatinimas Naudojant Pasyvià Ir Aktyunclassified
“…Jo vie na sri tis jun gia si su Ab1-10 ami no rûgð èiø se ka, o ki ta -su Ab16-26 re gio nu [32]. Gan te re nu ma bas ska ti na se ni li niø plokð te liø ar dy mà, ak ty vuo da mas mik ro gli jà ir fa go ci to zae, ta èiau ne si jun gia su plaz mos be ta ami loi du.…”
Section: Amiloido Beta ðAlinimo Skatinimas Naudojant Pasyvià Ir Aktyunclassified
See 2 more Smart Citations